CIA-CIA LANGUAGE: FROM THE ERA OF ORAL TO THE ERA OF WRITING - Cho, Tae-Young (Humaniora, 2012)
This paper aimed to describe the background of Cia-Cia language society's adoption and use  of Hangeul (Korean alphabet) as its writing system that was begun in July 2009. The issue has caused Indonesian society and neighborhood countries curious, since Latin alphabet is world widely used as the most common writing system at present time. On the other side, the historical background of writing system's development which has been implemented sustainably through borrowing and adapting process proves that any writing system can also be used in other language society in the 21st  century. Similar to that of the most of minority language societies, Cia-Cia language has not had its own writing system. The transcription of Hangeul in Cia-Cia language was begun to support the preservation of minority language. Concern to this issue, if the spoken language of Cia-Cia is stabilly continued, Hangeul will be known as one of the writing systems which has preserved Cia-Cia language in world's development of writing system history.